Melanoma and squamous cell carcinoma developing on a burn scar - Ostojić, Nikola; Stepić, Nenad; Rajović, Milica; Končar, Jovana; Novaković, Marijan (Vojnosanitetski pregled, 2022)
Introduction. Development of malignancy in chronic burn scars is described in 2% of cases, with cutaneous squamous cell carcinoma (cSCC) being the most frequent. It develops several years after the burn injury, as a consequence of malignant transformation in chronically inflamed tissue. Melanoma in a burn scar is, however, quite rare; in several cases, a synchronous or metachronous appearance of melanoma and cSCC was noted. Based on the previous rare reports, melanoma and cSCC can concurrently arise on thermal burn scars, as well as on the areas treated with skin grafts. Case report. We reported a case of a 67-year-old male who was accidentally scalded by boiling water at the age of 14. The patient subsequently developed melanoma at the age of 60, according to clinical and dermoscopic examination at the site of the burn scar, and after excision and histopathological analysis, the diagnosis of melanoma was confirmed (superficial spreading melanoma, Breslow 0.87 mm, with ulceration, pT1b). Complete surgical excision was done, and the diagnosis was confirmed with histopathological analysis. After the diagnosis of melanoma, regular follow-up every six months was scheduled, and three years later, cSCC was suspected and confirmed after surgical excision and histopathologic analysis. Conclusion. This case highlights the importance of long-term dermatological follow-up after burn injuries and early detection and treatment of skin cancer that can lead to better outcomes in these patients.